Strategi Pemberdayaan Masyarakat dalam Pengembangan Perekonomian melalui Pemanfaatan Wisatawan Asing di Desa Ngadisari - Septiandika, Verto; Maksin, Mastina; Yunus, Eko Yudiyanto; Puspitarini, Renny Candra; Sucahyo, Imam; Fadilah, Siti Nur (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
This community service aims to empower the residents of Ngadisari Village in economic development through the utilization of foreign tourists. This topic was chosen because, although the natural tourism potential, such as Mount Bromo and Seruni Point, has been utilized, further development is still needed. The method used is descriptive qualitative, which includes interviews and observations to understand the conditions and needs of the community. The results of the community service show that skills training, local product development, and promotion of the village's natural beauty can attract more tourist interest, positively impacting the community's income. Active community involvement in tourism development also enhances a sense of ownership and sustainability of initiatives. In conclusion, community empowerment through foreign tourism not only boosts the local economy but also strengthens the village's cultural and social identity.